MODEL OF AGROECOSYSTEM IN JEMBER REGENCY - Nurul Sumiasri (Universitas PGRI Semarang, 2011)
The objective of this study to know several models of agro-ecosystems in Jember regency.Study about model of Agro-ecosystem of Jember regency was carried out at seven districts in Jember regency i.e Ambulu, Gumukmas, Tempurejo, Bangsalsari, Jeng-gawah, Rambipuji and Puger during January to February 2011. The method of this study was survey to 10 respondents (head families), the respondents were taken by sampling in each district. The primary data were collected with direct observation and interview with respondents (KK), while the secondary data, collected with study literature and internet orientation. Data analyzed with D & D method.The results showed that there were six (6) models of agro-ecosystem which can be found in Jember regency i.e irrigation rice field, dry area, home gardens, fish pond, coastal pond and plantation.Key words: Agroecosystem, model, Jember regency